Eurocentric Historiography: An Analysis of International Politics in the 21st Century and Its Effect on Changes in Historiography of Countries in Europe - Joseph Geraldo; Michael Etnan (GoAcademica Research & Publishing, 2023)
History is a form of the collective memory of societies. The history of any society is not independent of others. Historiography traditionally focused on relations among political authorities, namely, states. Within this context, societies had been equated with states. Geographical discoveries, which began at the end of 15th century, culminated in the emergence of a Eurocentric view of world history. The development of Eurocentric historiography was not an outcome of convention, but rather a reflection of world politics at that time. Historians began to write history by treating states dominant at regional and global scale as basic to their work. In this study, it is explained that international politics has had an important role in the development of Eurocentric historiography. To this end, historiography and the links between society and modern states are examined; the development of the Eurocentric international system is reviewed; the re-construction of non-European society by modern states is assessed; whether or not non-European societies are capable of an alternative historiography is debated; and, finally, it is claimed that modern international practices have determinative influence in the development of Eurocentric historiography.